Speaking for the people : Native writing and the question of political form - Rifkin, Mark, 1974- (Duke University Press, 2021)
"Mark Rifkin examines nineteenth-century Native writings by William Apess, Elias Boudinot, Sarah Winnemucca, and Zitkala-Ša to rethink and reframe contemporary debates around recognition, refusal, and resurgence for Indigenous peoples."--